1992
DOI: 10.1161/01.cir.85.2.790
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic effects on the biology of the adult mammalian cardiocyte.

Abstract: Background. To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
397
0
16

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 777 publications
(424 citation statements)
references
References 50 publications
6
397
0
16
Order By: Relevance
“…Myocyte loss can occur via toxic mechanisms, producing necrosis, or by programmed cell death, producing apoptosis (9). There is experimental evidence that myonecrosis might be triggered by elevated levels of circulating or tissue norepinephrine, or by excessive stimulation with angiotensin II or endothelin (25,26). It has been proved in in vitro and in vivo models that apoptosis can be triggered by multiple factors taking part in the pathogenesis of heart failure, such as myocardial stretch, norepinephrine, TNF, oxidative stress, angiotensin II.…”
Section: Changes At the Myocyte And Myocardium Levelmentioning
confidence: 99%
“…Myocyte loss can occur via toxic mechanisms, producing necrosis, or by programmed cell death, producing apoptosis (9). There is experimental evidence that myonecrosis might be triggered by elevated levels of circulating or tissue norepinephrine, or by excessive stimulation with angiotensin II or endothelin (25,26). It has been proved in in vitro and in vivo models that apoptosis can be triggered by multiple factors taking part in the pathogenesis of heart failure, such as myocardial stretch, norepinephrine, TNF, oxidative stress, angiotensin II.…”
Section: Changes At the Myocyte And Myocardium Levelmentioning
confidence: 99%
“…Amphetamine has been shown to induce apoptosis in fetal rat neocortical neurons (Stumm et al, 1999) and in PC12 cells (Oliveira et al, 2002) in a process generally considered to be associated with increased stress and formation of reactive oxygen substances. Moreover, the ephedrine-related catecholamine, norepinephrine, induces apoptosis in cardiac myocytes (Singh et al, 2001) by binding to b-adrenergic receptors through a mechanism that is dependent on activation of cyclic AMP-dependent protein kinase (Mann et al, 1992;Communal et al, 2000).…”
Section: Hl-60mentioning
confidence: 99%
“…α-Adrenergic receptor mediated effects and consequences of increased norepinephrine concentrations have proven to be vicious effects of increased sympathetic tone. 15,17 It was demonstrated that carvedilol, a combined α-and β-adrenergic receptor blocker had superior hemodynamic and metabolic effects compared to single β1-receptor blockade in conscious dogs with dilated cardiomyopathy and clear sympathoexcitation. 18 These results were in accordance with those obtained in the carvedilol or metoprolol european trial (COMET) trial, which compared carvedilol and metoprolol.…”
Section: Discussionmentioning
confidence: 99%